Sustainable cultivation and harvesting strategy for Spirulina biorefinery: integrating internet-of-things monitoring and continuous cultivation - Lim, Hooi Ren (2024)
Spirulina biomass accounts for 30% of the total algae biomass production globally. In conventional process of Spirulina biomass production, cultivation using chemical-based culture medium contributes 35% of the total production cost. Moreover, the environmental impact of cultivation stage is the highest among all the production stages which resulted from the extensive usage of chemicals and nutrients. Thus, various types of culture medium such as chemical-based, modified, and alternative culture medium with highlights on wastewater medium is reviewed on the recent advances of culture media for Spirulina cultivation. This creates an opportunity for the development of sustainable practices for the cultivation of Spirulina.